Relatório de Estágio Supervisionado Obrigatório: Instituto de Desenvolvimento Agropecuário e Florestal Sustentável do Estado do Amazonas - IDAM - Reis, Anna Cássia da Silva (Brasil, 2024)
This is a report drawn up from the Compulsory Supervised Internship carried out at the Institute for Sustainable Agricultural and Forestry Development of the State of Amazonas (IDAM), Parintins/ Amazonas unit. The internship lasted from May 6, 2024 to July 26, 2024, with a workload of 300 hours. This report seeks to describe the practical activities carried out during this period, which included renewing the primary producer card (CPP), collecting fishermen's signatures on AFEAM financing contracts, carrying out fish price research at fairs and supermarkets and a survey of aquaculture in the municipality of Parintins, which helped to establish a relationship between theory and practice in terms of the knowledge built up during the Zootechnics degree, contributing important lessons for professional life.